Herpetospermum motuoensis (Cucurbitaceae), a new species from Xizang, China - Zhang, Bu-Yun; Liu, Hou-Zhou; Xu, Ye-Chun; Song, Zhu-Qiu; Chen, You-Sheng (Phytotaxa, 2025)
Herpetospermum motuoensis (Cucurbitaceae: Schizopeponeae) is described and illustrated as a new species. It is similar to Herpetospermum operculatum but can be easily distinguished by the inconspicuous bracts of the male flowers (vs. bract of male flowers prominent), petals subrounded to elliptical (vs. petals ovate to obovate), ovules 6 per locule (vs. ovules 8 per locule), stigma subrounded to broadly elliptic (vs. stigma oblong–ovate), fruits are chartreuse, fusiform to ellipsoid–fusiform and glabrous (vs. oblong to ellipsoid–fusiform and pubescent), seeds are irregular oblong-hexagonal, margin with protrusion at each corner (vs. seed ± round, margin with irregular acute erose).